Use of Matrigel in culture affects cell phenotype and gene expression in the first trimester trophoblast cell line HTR8/SVneo - Highet, A.R.; Zhang, V.J.; Heinemann, G.K.; Roberts, C.T. (Placenta (Eastbourne), 2012)
There is inconsistent use of Matrigel for experiments with the HTR8/SVneo first trimester trophoblast and other cell lines. We quantified the effects of Matrigel on the expression of genes considered to be markers of extravillous cytotrophoblast (EVT) differentiation and invasive potential. Culture on Matrigel promoted formation of “endothelial-like” tubes and reduced mRNA expression of matrix metalloproteinase 2 (MMP2), cytokeratin 7 (KRT7) and integrin alpha 1 (ITGA1), while increasing VE-cadherin (CDH5) expression consistent with a vascular phenotype. This process may constitute part of the endothelial cell mimicry exhibited by endovascular EVTs invading the maternal spiral arteries. HTR8/SVneo appears to be phenotypically polymorphic and adopt endovascular morphology on Matrigel.